CYTOKINE PROFILE IN PREGNANT WOMEN WITH METABOLIC DISORDERS - T. S. Prokhorenko; A. P. Zima; T. V. Saprina; V. V. Novitskiy; N. M. Todosenko; L. S. Litvinova (Медицинская иммунология, 2017)
Serum concentrations of cytokines (IL-2, IL-6, IL-8, IL-10, GM-CSF, IFNγ, TNFα) were determined in blood serum of pregnant women with different types of metabolic disorders, i.e., gestational diabetes, obesity, and a combination of those disorders. The study was performed by means of flow fluorimetry, using a multiplex test system. Changes of cytokine profiles in pregnant women with overweight or obesity, and pregnant women with gestational diabetes showed some similarities. In pregnant women with overweight or obesity we have found an increase in blood concentrations of IL-2, IL-6, IL-10, IFNγ, and TNFa. Meanwhile, an increase in blood levels of IL-2, IL-6, IL-10 and TNFα was revealed in pregnant women with gestational diabetes. The changes in cytokine profile were most pronounced in cases of pregnancy complicated with gestational diabetes and obesity. In these women, increased IL-6, TNFα, GM-CSF and IFNg concentrations were revealed in blood, along with low contents of IL-2 and IL-10. Potential causes and consequences of suggested subclinical inflammation in pregnant women are discussed. We conclude that pregnant women with metabolic disorders may develop a subclinical inflammation at the early stages of obesity, or metabolic disturbances.